Числово-аналітична методика дослідження фазового складу та залишкового напруженого стану пластин з низьколегованої сталі при локальному високотемпературному нагріві - Гачкевич, Олександр; Козакевич, Тереза; Гаєк, Максиміліан (КІНПАТРІ ЛТД, 2013)
The numerically-analytical three-stepped procedure variant of research of residual phase and stress states of thin plates subjected to local heating by moving distributed sources with several centers of localization and following monotonic cooling is proposed.
The numerically-analytical procedure of research of the phase content and residual stress state of low-alloyed steel plates under local high-temperature heating